2014
DOI: 10.1016/j.envint.2014.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to elemental constituents of particulate matter and cardiovascular mortality in 19 European cohorts: Results from the ESCAPE and TRANSPHORM projects

Abstract: In a joint analysis of 19 European cohorts, we found no statistically significant association between long-term exposure to 8 elemental constituents of particles and total cardiovascular mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 42 publications
1
88
0
4
Order By: Relevance
“…The European studies focused on elemental composition and did not present results for carbon-containing components (i.e., OC, EC, and/or BC or black smoke). None of the elements studied, including S, which can serve as a marker for sulfate, was significantly related to pediatric respiratory outcomes Eeftens et al, 2014) or to cardiovascular mortality (Wang et al, 2014). The U.S. papers that considered mortality or adverse cardiovascular outcomes, with the exception of Lipfert et al (2009), reported significant associations with sulfate; all of these papers reported significant associations with some organic components.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The European studies focused on elemental composition and did not present results for carbon-containing components (i.e., OC, EC, and/or BC or black smoke). None of the elements studied, including S, which can serve as a marker for sulfate, was significantly related to pediatric respiratory outcomes Eeftens et al, 2014) or to cardiovascular mortality (Wang et al, 2014). The U.S. papers that considered mortality or adverse cardiovascular outcomes, with the exception of Lipfert et al (2009), reported significant associations with sulfate; all of these papers reported significant associations with some organic components.…”
Section: Discussionmentioning
confidence: 92%
“…Three of these papers (Wang et al, 2014;Fuertes et al, 2014;Eeftens et al, 2014) Two studies considered reproductive endpoints in California cohorts. Wilhelm et al (2011) studied a cohort of births from about 110,000 women who lived within 5 miles of an air pollution monitor in southern California from June 2004 through March 2006.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for the first time, particulate matter (PM), a major component of outdoor air pollution, was "evaluated separately and classified as carcinogenic to humans" (Group 1, Beelen, Raaschou-Nielsen [2]) since an increasing risk of lung cancer with increasing levels of exposure to PM and air pollution was found whatsoever the PM chemical composition. Moreover, scientific evidences also allowed to recognize the PM as responsible of cardiovascular death due to long-term exposures [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The coordination in Denmark was selected from the experiences with mother-child cohorts and adverse effects of air pollution (18,19). The Czech partners were leading in human biomonitoring and air pollution (20)(21)(22) as well as socioecomomic research on health risks benefits (23)(24)(25)(26) and consumer behavior (27).…”
Section: Newdanubementioning
confidence: 99%